2011
DOI: 10.1136/bjo.2010.201699
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of sulfur hexafluoride (SF6) versus perfluoroethane (C2F6) gas tamponade for non-posturing macular-hole surgery

Abstract: Macular-hole surgery with SF(6) gas achieves similar results to C(2)F(6) and is absorbed faster, allowing quicker visual rehabilitation for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…There is general consensus that ILM peeling improves primary anatomical hole closure rate and is now widely practiced but some surgeons do not peel ILM if hole size is <400 μm because of the potential of iatrogenic harm from the peeling procedure [3,4,13,14]. The need for posturing is debated with many studies showing successful non-posturing surgery in holes <400 μm and often with the use of short-acting gases [5,15,16,17,18]. Large holes are still usually treated with longer-acting gases and posturing [5,6,7,19,20] although the requirement for posturing is debated and a further study is needed [21].…”
Section: Discussionmentioning
confidence: 99%
“…There is general consensus that ILM peeling improves primary anatomical hole closure rate and is now widely practiced but some surgeons do not peel ILM if hole size is <400 μm because of the potential of iatrogenic harm from the peeling procedure [3,4,13,14]. The need for posturing is debated with many studies showing successful non-posturing surgery in holes <400 μm and often with the use of short-acting gases [5,15,16,17,18]. Large holes are still usually treated with longer-acting gases and posturing [5,6,7,19,20] although the requirement for posturing is debated and a further study is needed [21].…”
Section: Discussionmentioning
confidence: 99%
“…Most studieson this topic confirm the ophthalmologists preference for gas tamponade in the last 15 years (19). Air tamponade is the most often technique used in vitreoretinal surgery for retinal detachment, vitreous haemorrhage, epiretinal membrane etc.…”
Section: Treatmentmentioning
confidence: 80%
“…Seven days positioning also implies significant higher medical and social costs, poorer compliance and major patient discomfort. Se recent studies analysed the posibility of avoiding dorsal postoperative positioning and the good outcomes suggest that positioning is less important as long as the surgical technique is very good (19,22). However, these results need to be confirmed by future similar studies.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4,11,12,[24][25][26][27][28] The results of recent comparative studies 12,[26][27][28] suggested no statistically significant difference in the closure rates between no posturing or short-term posturing and standard posturing. However, there was a tendency for the closure rate to be better with standard posturing than with no or short-term posturing, for example, posturing versus no posturing was 97.4% versus 87.5% in a study by Guillaubey et al 26 27 Nonetheless, these results must be questioned because 800 cases are theoretically required to achieve a 95% confidence interval.…”
Section: Discussionmentioning
confidence: 99%